Characteristics of Extreme Heat Events in Vietnam: Statistical Overview Through Md Index and Lagrangian Analysis - Nguyen Quynh Hoa, Dao; Duc Thang, Nguyen (VNU Journal of Science: Earth and Environmental Sciences; Vol 42 No 2DO - 10.25073/2588-1094/vnuees.5353, 2025)
Abstract: The study investigates the heat extreme events characteristics across seven subregions of Vietnam from March to September using ERA5 reanalysis data for the period 1981 – 2024. The characteristics of heatwaves are determined from the dimensionless heatwave index M d , which standardizes the exceedance level of daily maximum temperature (Tx) relative to its percentile threshold. Results reveal an increase in frequency, duration, intensity, and spatial extent, with notable regional disparities, particularly in the Northwest, Central Vietnam, Central Highlands, and Southern regions during study period. A prolonged April 2024 extreme heat event, with record coverage over the entire subregions of Vietnam, was driven by joint influence of the Bay of Bengal anticyclone and the western North Pacific subtropical anticyclone. Backward trajectory analysis (in Lagrangian methodology) revealed two air parcel origins: continental (dry, foehn-enhanced) and oceanic (humid), whose interation amplified heat intensity and scale. These findings highlight multi-mechanism drivers of extreme heat condition in Vietnam and underscore the importance of integrating synoptic and Lagrangian analyses for improved forecasting and climate adaptation.